ESG did not immunize stocks during the COVID-19 crisis: a study based on Brazilian companies listed in the index portfolio - ISE B3 - OLIVEIRA, Ana Virginia Aragão de (2023)
The COVID-19 pandemic generated an unparalleled stock market crash in 2020. Considering that the Brazilian financial market faced an unprecedented scenario combined with the high volatility of stock prices caused by the uncertainties of the crisis, it is a unique opportunity to evaluate the ESG performance as a factor of protection for stock prices. This research aims to analyze whether the ESG score was a determining factor for the protection of stock prices during the period of the COVID-19 pandemic, specifically during the market crash in 2020 (March 2020) and for the full year of 2020, comparing the companies that are part of the ISE B3 portfolio from Ibovespa with those not listed in this portfolio. For this, data were collected on the Refinitv Eikon® platform, and an analysis was performed using the event study methodology for both periods. This research shows that, due to the abnormal return regressions, companies with ESG scores listed in the ISE B3 portfolio did not show statistically significant results during the 2020 COVID crisis, specifically in March of 2020. It is concluded that ESG did not immunize stocks during the COVID-19 crisis.